Development of a short form of the Greek Big Five Questionnaire for Children (GBFQ-C-SF): Validation among preadolescents. (1st July 2017) - Markos, Angelos; Kokkinos, Constantinos M.
Abstract: The Big Five Questionnaire for Children (BFQ-C) is a relatively new 65-item scale for assessing the Five Factor Model (i.e. Energy/Extraversion, Agreeableness, Conscientiousness, Emotional Instability, and Intellect/Openness) in childhood and early adolescence. The BFQ-C has been validated in several languages, including Italian, Dutch, German, Spanish and Greek. Nonetheless, its applicability may be limited by its length. This study derived an abbreviated form of the Greek translation of the BFQ-C, using techniques from both classical test theory and item response theory. The shortened form of the Greek BFQ-C (GBFQ-C-Short Form) included 30 items, with 6 items per subscale. The five-factor structure of the original BFQ-C was validated for a sample of Greek preadolescents and was used to develop the shortened version, which was then cross-validated using a second, independent sample. Results highlighted that the GBFQ-C-SF has equivalent psychometric properties compared with the full version and showed strong convergence with theoretically-relevant external criteria. Highlights: Short-form version of the Greek Big Five Questionnaire for Children (GBFQ-C-SF) GBFQ-C-SF has satisfactory construct validity and internal reliability. Evidence for convergent validity with theoretically-relevant constructs was obtained. Promising instrument for measuring the FFM in childhood and early adolescence